The Importance of Fracture Liaison Services to the Healthcare System: A Review - Patel, Shaan; Daniels, Natasha F.; Lim, Jiang An; Zhou, Andrew Kailin; Thahir, Azeem; Krkovic, Matija (Current Rheumatology Reviews, 2023)
Osteoporosis is an important public health concern, with secondary fragility fractures carrying a poor prognosis. The role of a Fracture Liaison Service (FLS) is to identify fragility fracture patients via investigation and risk assessment. This serves to address the osteoporosis treatment care gap that exists where the majority of patients with a new fragility fracture over 50-years-old fail to receive a bone mass density (BMD) scan and osteoporosis treatment, ultimately receiving inadequate care. Osteoporosis medication is effective in reducing secondary fragility fractures. However, treatment adherence poses a problem. The FLS serves to prevent more serious secondary fragility fractures such as hip fractures. This minimises operative costs and the cost of postoperative care and results in fewer secondary care and care home admissions, increasing healthcare savings. Implementation of the FLS is effective in increasing investigation, treatment initiation, and adherence, with a corresponding decrease in refracture rate and mortality. This paper aims to evaluate the previous osteoporosis treatment care gap, the effectiveness of osteoporosis medications currently available, and finally, the cost and clinical effectiveness of the FLS serving as a secondary prevention tool.
Keywords: clinical effectiveness